The maternal healthcare landscape around Grabouw, South Africa: Setting the stage for information systems development - Tswane, Siphokazi; Korpela, Mikko; M’Rithaa, Doreen KM; Kabaso, Boniface (Journal of Health Informatics in Africa, 2015)
Background and Purpose: The purpose of the paper is to depict the most essential aspects of the “landscape” of authorities, organizations and service flows related with maternal healthcare from the viewpoint of the local communities in the small town of Grabouw in Western Cape, South Africa. Understanding the wider landscape is needed for understanding the “close-up” view of the maternal healthcare services and activities in place in Grabouw, which in turn is a prerequisite for co-designing ICT based tools for the caregivers. Methods: The methodology for depicting information systems landscapes was applied in guiding the data collection and in analyzing the data. Data was collected from public sources (government documents, web sites, literature) and from administrators and educators with general knowledge.. Results: The geo-political structure around Grabouw consists of municipalities, districts, and the province of Western Cape within the republic of South Africa, all of which have elected structures with overall political authority. The structure of healthcare authority differs from the structure of political authority – the provincial Department of Health and not the local municipality is in charge of all healthcare facilities. The flow of healthcare services beyond Grabouw is defined by the referral system, which in principle is aligned with the political structure but is adjusted to particular geographic factors. Within the Grabouw community the service flow is guided by proximity of care and the preferred services. Conclusions: The results show that it is vital to understand the ‘healthcare landscape’ and the context around maternal care in Grabouw. There is an overlap of geo-political and healthcare authority structures, and information systems developers need to aware in order to develop useful, effective and efficient ICT solutions. The landscape model has proven to be successful in understanding the different elements of a ‘landscape’ around a community.